Social media influence on politicians' and citizens' relationship through the moderating effect of political slogans - Fatema, Shafaq; Yanbin, Li; Fugui, Dong (Frontiers in Communication, 2022)
The digitalization of communication means has revolutionized the way people observe and react to the social and political developments in their surroundings. The rapidly growing influence of social media prompted this exploratory research article on the use of social networking sites by politicians to build a cordial and strong relationship with the common citizens. This article focuses on investigating social media's influence on the relationship between politicians and citizens through the moderating effect of political slogans. Social media not only enables the politicians to directly communicate with the citizens but also encourages political participation of citizens in the form of feedback via comments on social networking sites. Political slogans play a significant role in the image building of a particular political force in the eyes of citizens. A quantitative analysis approach is utilized in this study. Data are collected via a survey questionnaire from a variety of social media users with a cross-sectional time horizon. In total, 300 people submitted their responses via the questionnaire, which was circulated in the first 2 months of this year (i.e., January and February 2022). The convenience sampling method was utilized for data collection across two cities in Pakistan. Smart PLS 3 has been used for hypothesis testing. The effect of the Moderator, i.e., political slogans of the basic four political parties of Pakistan are measured individually. Results show that the impact of social networking sites and politics on politicians' and citizens' relationships is positive and significant. This study can be a stepping stone for further related research to enable the politicians to make positive relationships with the citizens by effectively utilizing the social media platform.